2021
DOI: 10.3390/journalmedia2010001
|View full text |Cite
|
Sign up to set email alerts
|

Intersections between TikTok and TV: Channels and Programmes Thinking Outside the Box

Abstract: The rise of the TikTok social network has caused the media to confront the younger generation. The platform, which hosts dances, challenges, and funny short videos, has unique features that force a reinvention of social networking strategies. Television has become social and has expanded to new platforms, while young people are abandoning the consumption of traditional television. In this study, we explore—for the first time—the presence of television channels and programmes on TikTok and an analysis of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 49 publications
0
6
0
3
Order By: Relevance
“…The research [27] indicates that the social network TikTok is one of the most used media by the young generation; in this study, we found that TikTok has accessibility barriers that make it difficult for all people, including young people, to navigate the application; the most frequent error is related to touch target.…”
Section: Discussionmentioning
confidence: 70%
“…The research [27] indicates that the social network TikTok is one of the most used media by the young generation; in this study, we found that TikTok has accessibility barriers that make it difficult for all people, including young people, to navigate the application; the most frequent error is related to touch target.…”
Section: Discussionmentioning
confidence: 70%
“…Esta consideró destacados trabajos, publicados en revistas indexadas a las bases de datos WoS y Scopus, que muestran importantes elementos a la hora de realizar un análisis de cómo se publica en esta red social. Así, se valoraron las condiciones para establecer paralelos entre TikTok y la televisión (Vázquez-Herrero et al, 2021) y en consecuencia al señalado estudio, se analizaron trabajos que permiten establecer categorías para los videos de ciencia y el contenido que predomina en esa red social (Zeng et al, 2021), además de considerar investigaciones centradas en el engagement con los usuarios (Li et al, 2021), valorando la cantidad de likes, comentarios o veces compartida que tiene una publicación.…”
Section: Materials Y Métodosunclassified
“…Esto último, puede estar asociado a un concepto que puede ser conocido como periodismo replicante (Costa-Sánchez et al, 2015), el cual se refiere al hecho de que se ofrece el mismo contenido informativo, a pesar de que está dirigido a distintos usuarios y en distintas plataformas. En el caso puntual de TikTok, los programas informativos que han comenzado a experimentar con esta plataforma encuentran dificultades en adaptar sus contenidos a esta red social (Peña-Fernández et al, 2022), y la mayoría de los canales no tiene una estrategia adecuada para enfrentarse a esta aplicación (Vázquez-Herrero et al, 2021), lo que lleva a replicar contenidos que no aprovechan el lenguaje propio y posibilidades narrativas de una plataforma tan reciente como TikTok.…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation
“…and it most recently demonstrated that it drives and shapes the news, which was highlighted through its coverage of the 2022 trial between Johnny Depp and Amber Heard (Sicha, 2022). Its influence extends beyond social media because the trends that first appear on social media filter out reliably to television and other communication channels (Vázquez-Herrero et al , 2021).…”
Section: What Is Tiktok?mentioning
confidence: 99%